Pseudomixoma peritoneal: abordagem cirúrgica em dois casos - Costa,Olívio Louro (2002)
The authors report the surgical procedure in two patients with pseudomyxoma peritonei, histologically considered as mucinous adenocarcinoma. In both patients, intestinal loops and other visceras were blocked and it was not possible to localize the tumor's origin. There was, in both cases, a great volume of mucinous ascitis. In the first patient a laparotomy was performed and a drainage by a five centimeters peritoneostomy in the abdominal upper left quadrant. In the second just a peritoneostomy was performed in the same location. The sequential irrigation of the abdominal cavity controlled the ascitis in a few days. Certainly this approach avoided a second procedure to clean the mucinous ascitis.